2011
DOI: 10.1517/17425255.2011.608660
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacogenetics of antimalaria artemisinin combination therapy

Abstract: Translation in this moment is not operationally possible at an individual level, but large population studies are achievable for: i) the development of robust pharmacogenetics markers; and ii) the parallel development of a pharmacogenetic cartography of malaria settings. Advances in the understanding of antimalarial pharmacogenetics are urgent in order to protect the exposed populations, enhance the effectiveness of ACT and, consequently, contributing for the long aimed elimination of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 118 publications
1
18
0
Order By: Relevance
“…In the present study, CYP2B6*6 polymorphism was not associated with AM elimination. While intestinal CYP3A4 might play a role in the presystemic metabolism of AM (43,44), interaction studies indicated that liver CYP3A4 is not important in the in vivo metabolism of AM (28). This is in line with our finding that there was no difference in CL according to genetic variations of CYP3A4.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, CYP2B6*6 polymorphism was not associated with AM elimination. While intestinal CYP3A4 might play a role in the presystemic metabolism of AM (43,44), interaction studies indicated that liver CYP3A4 is not important in the in vivo metabolism of AM (28). This is in line with our finding that there was no difference in CL according to genetic variations of CYP3A4.…”
Section: Discussionsupporting
confidence: 90%
“…In Cambodia, however, its efficacy since 2002 has been reported in all but one study to be considerably and consistently lower (19,20,21). While the influence of nongenetic factors, such as food intake, age, or body weight, on the pharmacokinetics of antimalarial drugs has received some attention, only more recently have the effects of polymorphisms in genes encoding enzymes responsible for antimalarial drug metabolism (such as CYP, NAT2, and UDPglucuronosyltransferase [UGT] gene), received attention (22)(23)(24)(25)(26)(27)(28). Better knowledge of the ethnic variability of genes encoding metabolizing enzymes, and of the impact of this variability on the pharmacokinetic profiles of antimalarial drugs, could help tailor treatments for specific populations.…”
mentioning
confidence: 99%
“…Elevated levels of estrogens, progesterone, cortisol, and prolactin hormones during pregnancy have been linked to altered metabolic activity of several hepatic cytochrome P450 enzymes. For instance, catalytic activity of CYP3A4, CYP2C9, and CYP2A6 enzymes increases during pregnancy (10,11), and these enzymes are responsible for lumefantrine and artemether metabolism (12,13). Hence, it is expected that significant alteration of the pharmacokinetics (PK) of most antimalarial drugs during pregnancy occurs, which may be associated with lower drug concentrations and lower antimalarial cure rate, especially in advanced pregnancy (14)(15)(16).…”
mentioning
confidence: 99%
“…In contrast, concomitant oral administration of dihydroartemisinin (DHA) and mefloquine to healthy volunteers has been shown to have no effect on either partner drug, except for a slight increase in the absorption rate of mefloquine. Similarly, no alteration in the pharmacokinetic s of either atovaquone or proguanil was observed following concomitant treatment with artesunate (AS) in healthy adult volunteers [56].…”
Section: Partner Drug-drug Interactionmentioning
confidence: 99%